Estresse oxidativo sistêmico na obesidade canina: Gabriela Quideroli Issa. - - Issa, Gabriela Quideroli [UNESP] (2015)
Obesity is a nutritional disease becoming more common in small animals, whose prevalence has reached epidemic proportions. This disorder has been associated with various diseases, affecting the quality of life and reducing the longevity of animals. In humans it is known that obesity is strongly associated with increased oxidative stress. A literature review on oxidative stress in obese dogs was conducted using two databases (CAPES Portal and PubMed) and was located just two experimental study in dogs that did not prove oxidative stress been described in humans. In this sense was a cross-sectional observational study with control to confirm our hiopótese that canine obesity causes sitêmico oxidative stress. For such a control group consisting of 19 healthy dogs (body condition score of 4 to 5) was compared to a group consisting of 25 obese dogs (body condition score of 8 and 9). Of both groups were measured the plasma oxidative stress markers (oxidative stress index (OSI), total oxidant concentration (TOC), total antioxidant capacity, lipid peroxidation, uric acid, albumin and gamma glutamyl transferase). t was possible to prove that there is an increase of systemic oxidative stress in canine obesity, characterized by increased lipid peroxidation and IEO associated with a higher concentration of TOC